Blockchain-Enabled Universal Health Records: An Architectural-Level Decentralized Framework for Secure Patient Data Interoperability - Venkata Sarath Maddali (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
Healthcare systems worldwide face critical challenges in patient data management, including fragmented medical records, limited interoperability between providers, security vulnerabilities, and patient privacy concerns. This paper presents a comprehensive framework for implementing blockchain-enabled Universal Health Records (UHR) that addresses these fundamental limitations through decentralized architecture and cryptographic security. Our proposed solution leverages distributed ledger technology to create a patient-centric ecosystem where individuals maintain sovereign control over their health data while enabling authorized healthcare providers to access complete, accurate medical histories in real-time. A pilot implementation across three healthcare facilities (n=150 patients) using traditional EHR systems demonstrated significant improvements: 67% reduction in patient record retrieval time (from 12.3 to 4.1 minutes), 89% decrease in data inconsistencies between providers, and 94% patient satisfaction with data access transparency. Security testing revealed zero unauthorized access attempts over 6 months, while maintaining 99.7% system uptime. Through comprehensive analysis of technical architecture, security protocols, and implementation strategies, this paper demonstrates how blockchain technology can transform healthcare data management, offering a technically feasible, economically viable, and regulatory-compliant pathway toward universal health record interoperability.